The Opportunities and Challenges of Islam-Muhammadiyah in the Implementation of Merdeka Belajar Kampus Merdeka - Yunita Furi Aristyasari; Muhammad Chirzin; Chusnul Azhar (AL-ISHLAH: Jurnal Pendidikan, 2023)
Merdeka Belajar Kampus Merdeka (MBKM) is a program designed to develop exceptional and prepared graduates to enter the community or the workforce. Islam-Muhammadiyah (AIK), as the speciality of Muhammadiyah colleges, seems to have "lost" its role of helping to put the MBKM program into place in higher education. This research is to explore the opportunities and challenges of AIK during the implementation of MBKM. This is qualitative research with a literature study method. The data was collected through the collection of library sources in the form of journal articles, books, and other references related to the theme. Content analysis is used to analyze, dissect, and interpret the data in a discussion about the opportunities and challenges of MBKM in AIK education. One of the opportunities for AIK to play an important role in the implementation of MBKM: a) college students are permitted to pursue AIK courses outside of their own study programs or institutions within the framework of Muhammadiyah colleges; b) AIK becomes a hue in every activity of the implementation of MBKM; c) AIK is one lecturer’s obligation (caturdharma). The challenges are a) the status of AIK is still regarded as quite unimportant and b) some disparities amongst Muhammadiyah universities. Muhammadiyah education and the higher education council must collaborate to give AIK a higher priority in the application of MBKM. Future research is expected to study the MBKM strategies in terms of AIK in Muhammadiyah colleges.